Creating Concise Summaries of Network Traffic Using Hierarchical Clustering - Mahmood, A; Leckie, C; Udaya, P (Bangladesh Journal of Scientific and Industrial Research, 2010)
In today's high speed networks it is becoming increasingly challenging for network managers to understand the nature of the traffic that is carried in their network. A major problem for traffic analysis in this context is how to extract a concise yet accurate summary of the relevant aggregate traffic flows that are present in network traces. In this paper we present two summarization techniques to minimize the size of the traffic flow report that is generated by a hierarchical cluster analysis tool. By analyzing the accuracy and compaction gain of our approach on a standard benchmark dataset, we demonstrate that our approach achieves more accurate summaries than those of an existing tool that is based on frequent itemset mining. Key words: Cluster analysis, Internet management, Traffic analysis, Summarization. DOI: 10.3329/bjsir.v44i3.4400 Bangladesh J. Sci. Ind. Res. 44(3), 281-288, 2009